The zombie wars eaudiobook We all fall down. - Talluto, Joseph (White Flag of the Dead, 2016)
The war on the zombies hasn't gone as expected. The army has been split into three parts, with Tommy and Duncan leading the charge through the southwest while John and Charlie deal with a problem that threatens the security of the entire campaign and the rest of the country. And all the while, a massive horde of zombies is moving its way across the plains, on a collision course with the survivors that will end only when one of them falls down for good.